1999
DOI: 10.1093/oxfordjournals.aje.a009775
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption, Cigarette Smoking, and Risk of Benign Prostatic Hyperplasia

Abstract: Alcohol consumption and cigarette smoking were evaluated in relation to development of benign prostatic hyperplasia (BPH) among 29,386 members of the Health Professionals Follow-up Study. Men who were 40-75 years old in 1986 and free of prior BPH surgery, diagnosed cancer at baseline, and prostate cancer at baseline and during follow-up were followed for incidence of BPH surgery from 1986 to 1994. Cases were men who reported BPH surgery between 1986 and 1994 (n = 1,813) or who scored > or = 15 points of 35 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
6
12

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 50 publications
9
96
6
12
Order By: Relevance
“…This is usually caused by cardiovascular or pulmonal problems, both related to smoking. Also, it has recently been reported that alcohol may have a protective effect on BPH, which may have resulted in an overestimation of the risk of alcohol drinking [21]. However, our data show that BPH patients do not drink less than bladder cancer patients or visitors at the urology ward which makes an overestimation of the risk of alcohol drinking unlikely.…”
Section: Discussioncontrasting
confidence: 52%
“…This is usually caused by cardiovascular or pulmonal problems, both related to smoking. Also, it has recently been reported that alcohol may have a protective effect on BPH, which may have resulted in an overestimation of the risk of alcohol drinking [21]. However, our data show that BPH patients do not drink less than bladder cancer patients or visitors at the urology ward which makes an overestimation of the risk of alcohol drinking unlikely.…”
Section: Discussioncontrasting
confidence: 52%
“…As a result of these and other difficulties, the knowledge of BPH risk factors is actually scarce [1, 2, 3, 4]. Alcohol intake has been suggested to be a risk factor for BPH by some authors [5]but others have negated such a role [6, 7, 8]. In the study of Chyou et al [6], intake of wine and beer was even inversely associated with obstructive uropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Androgens play a role in the development and maintenance of BPH particularly in the prostatic epithelium, which is supported by androgen receptor expression in prostatic epithelium [27]. Alcohol consumption is suggested to decrease testosterone concentrations and in some cases increase estrogens concentration hence higher susceptibility to BPH [28]. Our study suggested no influence of GSTT1 gene polymorphism and susceptibility to BPH.…”
Section: Discussionmentioning
confidence: 45%